2020
DOI: 10.1016/j.isci.2020.101085
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccinations Upregulate Myc, a Central Switch for Improved Glucose Metabolism in Diabetes

Abstract: Myc has emerged as a pivotal transcription factor for four metabolic pathways: aerobic glycolysis, glutaminolysis, polyamine synthesis, and HIF-1a/mTOR. Each of these pathways accelerates the utilization of sugar. The BCG vaccine, a derivative of Mycobacteria-bovis, has been shown to trigger a long-term correction of blood sugar levels to near normal in type 1 diabetics (T1D). Here we reveal the underlying mechanisms behind this beneficial microbe-host interaction. We show that baseline glucose transport is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…We therefore studied the effect of metformin and BCG in vitro in human monocytes ( Figure 5 ). Previous data suggest that metformin interferes with cytokines induced by BCG through innate immunity as well as with glycolysis pathways in innate and adaptive immunity ( Arts et al., 2016 ; Kühtreiber et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore studied the effect of metformin and BCG in vitro in human monocytes ( Figure 5 ). Previous data suggest that metformin interferes with cytokines induced by BCG through innate immunity as well as with glycolysis pathways in innate and adaptive immunity ( Arts et al., 2016 ; Kühtreiber et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This process of adaptive immune training can involve T cells as well as monocytes and centers on metabolic pathways that change aerobic glycolysis. Thus, the use and rate of sugar metabolism is improved after BCG therapy ( Kühtreiber et al., 2018 , 2020 ). The BCG effects observed in human autoimmune clinical trials have a slower onset of disease modifications (over years) but are permanent for >8 years in treated humans ( Kühtreiber et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 In addition, BCG causes an increase in glucose consumption in immune cells due to increased glycolysis and reduced oxidative phosphorylation, 60 , 61 thus helping to achieve glycemic control in type I diabetes patients. Kuhtreiber et al 62 recently reported for the first time, the effect of BCG vaccination in up-regulating the expression of Myc, an important transcription factor utilized by four metabolic pathways: glutaminolysis, HIF-1α/mTOR, glycolysis, and polyamine synthesis, all of which accelerate the utilization of glucose. Through this mechanism, BCG vaccination is able to trigger the correction of elevated blood glucose in type I diabetes patients.…”
Section: Bcg For Therapymentioning
confidence: 99%
“…Through this mechanism, BCG vaccination is able to trigger the correction of elevated blood glucose in type I diabetes patients. 62 In a recently published paper, Klein 63 described the findings of a retrospective analysis of two studies investigating the effect of BCG vaccination on the development of type I diabetes mellitus, and revealed that the administration of a booster dose of the BCG vaccine reinforcing postnatal BCG vaccination had a protective effect against type I diabetes, compared with post-natal BCG administration without booster dose administration. 63 In addition, the study noted that post-natal BCG administration without a booster was in turn better at protecting against type I diabetes than no BCG vaccination at all.…”
Section: Bcg For Therapymentioning
confidence: 99%